THE EFFECT OF METEOROLOGICAL UNDERSTANDING OF AERODROME CONTROL TOWER PERSONNEL ON AIR TRAFFIC SERVICES AT MAKASSAR AIR TRAFFIC SERVICE CENTER - KHANSA AULIA TRIDIANDINI; Lina Rosmayanti; Rini Sadiarmi (Jurnal Penelitian)
ATC personnel have an important role in the process of disseminating meteorological information for every phase of flight. The purpose of this study is to find out how much influence the meteorological understanding of ATC personnel has on air traffic services at Makassar Air Traffic Services Center. The quantitative research method is used by collecting data using questionnaires for ATC personnel and unstructured interviews with pilots at Sultan Hasanuddin International Airport in Makassar. The data processing used in this study is a correlation test, determination test, and simple linear regression. This study found the correlation coefficient is 0.79117 and the coefficient of determination is 62.6% which explains that understanding meteorology and air traffic services has a strong relationship and personnel ATC’s understanding of meteorology contributes 62.6% to air traffic services. Simple linear regression shows that for every additional 1 value of meteorological understanding, air traffic services will increase by 1.79111, the better the meteorological understanding of ATC personnel, the better the air traffic services at Makassar Air Traffic Services Center.